PERAN EDUKASI PEMERINTAH DALAM PEMBERDAYAAN MASYARAKAT BERBASIS LINGKUNGAN PERSPEKTIF PENDIDIKAN IPS DI KELURAHAN KEBUN KENANGA KECAMATAN RATU AGUNG KOTA BENGKULU - Meiki Sahputra; Desy Eka Citra Dewi; Sepri Yunarman (STKIP Subang, 2026)
Environmental problems in Indonesia, including those in Kebun Kenanga Urban Village, Ratu Agung District, Bengkulu City, remain a serious concern, reflected in the persistent practice of indiscriminate waste disposal, low community participation in cleanliness activities, and suboptimal community-based waste management. Although the local government has introduced various environmental education programs, public ecological awareness remains relatively low. This study aims to describe the role of government education in environment-based community empowerment, to identify the supporting and inhibiting factors affecting its implementation from the perspective of Social Studies Education, and to analyze the forms of community awareness resulting from such educational efforts. This research employed a qualitative descriptive approach, with the researcher acting as the primary instrument and participant observer at the research site. Data were collected through in-depth interviews, observation, and documentation, and were analyzed through data reduction, data display, and conclusion drawing, with validity ensured through source, technique, and time triangulation. The findings show that government education in Kebun Kenanga has been implemented through cleanliness socialization, counseling, and waste-bank programs, supported by the commitment of village officials, the availability of facilities, and the involvement of community leaders, but constrained by limited public literacy, budget limitations, and entrenched habits. These efforts have gradually fostered community understanding, caring attitudes, behavioral change, and collective independence in environmental management, reflecting the internalization of Social Studies education values such as mutual cooperation and social responsibility